A Review on the Current Progress and Challenges of 2D Layered Transition Metal Dichalcogenides as Li/Na‐ion Battery Anodes. Issue 13 (18th May 2021) - Sahoo, Ramkrishna; Singh, Monika; Rao, Tata Narasinga
Abstract: Energy storage systems play a crucial role to effectively utilize the recurrent renewable energy sources. In the last few decades, lithium‐ion battery (LIB) has emerged as the most convenient and viable energy storage systems and consequently, sodium‐ion battery (SIB) has drawn most of the attention of researchers as a potential alternative to LIB, especially in grid storage. Further development on LIB and SIB requires detection of novel electrode materials, precisely the anode. Captivating physico‐chemical properties and unique structure of layered transition metal dichalcogenides (TMDs) nanostructured materials have been rendered supremely appealing to the electrochemical energy conversion and storage devices researchers. In this review, synopsis of current state‐of‐art LIB and SIB anode materials, brief discussion on the different crystal structures and the common synthesis process of the TMDs have been articulated. Apart from these, detailed discussion on the electrochemical reaction and battery performance of different TMDs have been summarized and discussed in this review. The individuality of this review paper compared to the other reported review papers has also been highlighted in details. Finally, the challenges and limitations of the current TMDs materials, and outlook for the future improvement of TMDs in the energy sector have been proposed. Abstract : 2D anode materials : This review article summarizes the current state‐of‐art Li/Na‐ion battery anode materials based on 2D transition metal dichalcogenides (TMDs), discusses on the different crystal structures and the common synthesis processes of the TMDs, and on the electrochemical reaction and battery performance of different TMDs.